Object recognition and automatic selection in a Robotic Sorting Cell - Janse van Rensburg, Frederick Johannes (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2006.